Stress among final semester students in Universiti Teknologi Mara (UiTM) Kota Kinabalu campus / Putli Noor Asikin Datu Gulam - Datu Gulam, Putli Noor Asikin (Perpustakaan Tun Abdul Razak UiTM Caw Sabah, 2000)
This project paper is a survey on stress among the final semester students in UiTM Kota Kinabalu Campus. It was put together to comply with the requirement for the PAD 340 subject. The objectives of this study are to analyze factors (stressors) that caused stress among students, identify the characteristics of the students suffering from stress, analyze the academic performance among the students who may be suffering from stress related problem and attain the percentage of students who may be suffering from stress.